Production of Angkak Pigments by (Monascus - K H Timotius (Jurnal Teknologi dan Industri Pangan, 2004)
Monascus is one of the important molds for producing food colorants. Monascus produces non polar, semi polar, as well as polar food colorants and brown, red or yellow poliketide pigments. The production is usually done under solid state system, but various submerged system have been develop. Immobilized system showed prospective results. The pigments production is influenced by the availability of carbon and nitrogen sources, humidity, temperature, pH, and aeration. Poliketide pigments are used as food colorant in animal products, beverages, yoghurt, nata de coco, and daily home cooking practices. The stability of the pigments is influenced by temperature (various heating treatments), pH (acidity), oxygen, water activity, and light. Beside pigments, Monascus also produces various non-pigment metabolites, such as citrinin (a nephrotoxic agent), lavostatin (a hypocholesteremic agent), a monascidin (an antibacterial agent). Key word : Angkak, Monascus purpureus, natural pigment, polikatide pigment